A política de financiamento do banco mundial para a reforma do ensino médio no governo Temer - Fornari, Márcia (2020)
The dissertation entitled The world bank financing policy for the reform of high school in Temer’s government, aims to analyze the main measures adopted by the State to implement High School reform related to the financing policies that support and justify the High School reform adopted by Law 13,415 / 2017. This research was based on documentary analysis with emphasis on the reports of the World Bank: “Evaluation of the Social and Environmental Management System: Program to support the implementation of the New High School” (2017); “Skills and Jobs: An Agenda for Youth: Summary of policy findings, conclusions and recommendations” (2018); “Employment and Growth: The Productivity Agenda” (2018); “A Fair Adjustment: Analysis of the Efficiency and Equity of Public Spending in Brazil” (2018), as well as the “Loan Agreement for the reform of Secondary Education Nº 8812-BR 8813-BR” (2018), referring to the external financing policy for the implementation of the New Teaching between IBRD and Brazil, in addition to documents published by MEC, and SEED-PR, regarding the implementation of the reform of High School by the Law 13.415 / 2017. The development of the research constitutes an attempt to understand some of the contradictions present in the reform of High School. In this perspective, the financing policies for the reform of Secondary Education - Law 13.415, are presented as a project aligned with the recommendations of the World Bank and the Brazilian business community and are inserted in the set of projects and strategies that justify the Brazilian educational reforms with a view to meet the requirements of the logic that permeates the social and economic sectors, under the aegis of the ideological, political, economic and financial framework, demanded by the capitalist production method, at national and international level.